Faktor-Faktor yang Mempengaruhi Loyalitas - Yazid Yazid (Sinergi: Kajian Bisnis dan Manajemen, 2006)
Since competition is becoming more and more intense, loyalty is beliefed as the guarantee of the existence of a firm in the long term. Having customer loyalty does not only mean be the owner of a certain level of market share, but also have possession of potential return in the long term. However, loyalty is fragile. Low price, fast moving and better products, and also product availability are among the aspects considered as the sources of switching behavior of the customers Experts say that satisfaction must not be assumed as the end of marketing efforts, but loyalty is. Satisfaction is the mediating variable of quality and loyalty, means that quality is fundamental for a service firm to build customer loyalty or long-term competitive advantage.Therefore, even for service companies which own loyal customers, it is better for them to cautiously and insistently maintain their customers so that they will not go away to competitors. Since customers’ needs and wants are always changing over time, the key aspect to keep customers satisfied is understand well any type of service that the customers really need and want.Keywords: customer satisfaction, customer loyalty, customer delight, elements of loyalty, inte¬grated communication.